Carbon footprint of black tea products under different technological routes and its influencing factors - Zhang, Congguang; Ye, Xiaojie; Wu, Xiaoling; Yang, Xiong (Frontiers in Earth Science, 2023)
Tea industry is considered to have a high energy consumption, due to its complex life cycle system. The global change potential (GWP) of the life cycle of tea, is deserving in-depth discussion. This study conducted a life cycle assessment (LCA) towards the Dianhong black tea products, and evaluated the discharge and mitigation potential, and compared with the results of LCA of other tea to clarify the advantages and disadvantages of Chinese black tea industry. The results showed that the planting stage and packaging stage were the main sources of GWP in the life cycle of black tea, accounting for 43.73% and 39.44% respectively, because of the application of chemical fertilizer and the production of aluminum foil. In the tea processing stage, the GWP has a greater impact on the process of heating and withering, accounting for 8.63%. It is followed by the rolling stage, which accounts for 6.85%, mainly from the consumption of electricity during the process. Finally, the key factors affecting tea production efficiency and quality were analyzed by combining the results of contribution and sensitivity analysis. The research will contribute to the establishment of a more sustainable tea value chain.